Mixed-Mode Heat Training: A Practical Alternative for Enhancing Aerobic Capacity in Team Sports - Gale, Rachel M.; Etxebarria, Naroa; Pumpa, Kate L.; Pyne, David B. (Frontiers in Sports and Active Living, 2020)
Purpose: Heat training can be implemented to obtain performance improvements in hot and temperate environments. However, the effectiveness of these interventions for team sports during discrete periods of the season remains uncertain. Methods: We compared the effects of a short pre-season heat training intervention on fitness and thermal tolerance. In a counterbalanced crossover design, eleven state-level male football players undertook 6 x 60 min sessions in HEAT (35°C, 50% RH) and TEMP (18°C, 50% RH) conditions over 12 days. Running performance pre- and post- intervention was assessed via the Yo-Yo test (YYIR1), and thermal adaptation using a submaximal (4 x 4 min @ 9 – 13 km.h-1) treadmill heat stress test in 35°C, 50% RH. Results: Running distance increased by 9, ±9% in HEAT (standardized mean, ±90% confidence limits) and 13, ±6% in TEMP, the difference in the mean change between conditions was unclear (0.24, ±0.64 standardized mean, ±90% confidence limits). Irrespective of training interventions, there was an order effect indicated by a substantial 476 ± 168 m increase in running distance between the first and final Yo-Yo tests. There were trivial to small reductions in heart rate, blood lactate, RPE and thermal sensation after both interventions. Differences in mean core and skin temperature were unclear. Conclusions: Supplementary conditioning sessions in addition to sports-specific field-based training were effective in enhancing player fitness during the pre-season. However, few clear differences between HEAT and TEMP conditions indicate conditioning in the heat appeared to offer no additional benefit to that of training in temperate conditions.